Controlled Bacterial Lysis for Electron Tomography of Native Cell Membranes - Fu, Xiaofeng (Structure, 2014)
Cryo-electron tomography (cryoET) has become a powerful tool for direct visualization of 3D structures of native biological specimens at molecular resolution, but its application is limited to thin specimens (<300 nm). Recently, vitreous sectioning and cryo-FIB milling technologies were developed to physically reduce the specimen thickness; however, cryoET analysis of membrane protein complexes within native cell membranes remains a great challenge. Here, we use phage φX174 lysis gene E to rapidly produce native, intact, bacterial cell membranes for high resolution cryoET. We characterized E gene-induced cell lysis using FIB/SEM and cryoEM and show that the bacteria cytoplasm was largely depleted through spot lesion, producing ghosts with the cell membranes intact. We further demonstrate the utility of E-gene-induced lysis for cryoET using the bacterial chemotaxis receptor signaling complex array. The described method should have a broad application for structural and functional studies of native, intact cell membranes and membrane protein complexes.